1990
DOI: 10.1152/ajpheart.1990.258.5.h1432
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic reactivity of cerebral arteries in developing fetal lamb and adult sheep

Abstract: The response of cerebral arteries to norepinephrine was examined in vivo in six dated preterm fetal (94-121 days gestation), eight term fetal (127-141 days gestation), five newborn (7-14 days), and five adult sheep, anesthetized and equipped with a closed cranial window. Norepinephrine (10(-8)-10(-4) M in cerebrospinal fluid) caused a dose-dependent decrease in pial arteriolar diameter in fetal and newborn lambs; however, preterm fetuses were 7- and 14-fold more sensitive to norepinephrine than term fetuses an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
36
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 0 publications
3
36
1
Order By: Relevance
“…The latter is supported by data from chronic pial window studies in developing sheep, in which NE caused a dose-dependent arteriolar vasoconstriction mediated by ␣ 1 -adrenergic receptors. This response was most significant in preterm fetuses (94-121 days) and was not present in adult sheep (34). In adults and children, ϳ20% of infused dopamine is converted to NE, and dopamine also triggers release of stored NE from nerve endings (27), although sick preterm infants may not exhibit dose-dependent increases in NE during dopamine infusion (20).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The latter is supported by data from chronic pial window studies in developing sheep, in which NE caused a dose-dependent arteriolar vasoconstriction mediated by ␣ 1 -adrenergic receptors. This response was most significant in preterm fetuses (94-121 days) and was not present in adult sheep (34). In adults and children, ϳ20% of infused dopamine is converted to NE, and dopamine also triggers release of stored NE from nerve endings (27), although sick preterm infants may not exhibit dose-dependent increases in NE during dopamine infusion (20).…”
Section: Discussionmentioning
confidence: 97%
“…Ontogenic changes in the sensitivity of vascular beds to catecholamines have been described in several species, all of which suggest that ␣-adrenergic receptor development occurs first, followed by ␤-adrenergic and, finally, dopaminergic receptors. Wagerle et al (34) used the closed cranial window technique in developing sheep to demonstrate dose-dependent decreases in pial arteriolar diameter in response to NE. They showed that preterm fetuses are significantly more sensitive to NE than full-term fetuses and newborn lambs and that adult cerebral arterioles do not constrict at all (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…'l'he absence of endothelium-dependent relaxation in the immature cerebral circulation might effect an enhanced response to contractile stimuli. However, the fact that a functional cholinergic vasodilator capability was expressed in fetal early in fetal life (16). In addition to NO, alterations in P-adrenoceptor density and/or function in various vascular beds can changc significantly during aging (17)(18)(19)(20) and possibly modulate cerebrovascular reactivity to NE (21).…”
mentioning
confidence: 99%
“…In the cerebral circulation, this immaturity may be particularly important, because it may contribute to the high incidence of cerebrovascular complications observed in neonates (2,3). Among the few studies that have directly examined maturational changes in cerebral arteries, however, most have found that vasoconstrictor reactivity is generally higher in immature than in mature cerebral arteries (1,(4)(5)(6). Thus, the high incidence of neonatal cerebrovascular complications seems not to be a consequence of a deficit in the ability of cerebral arteries to respond to vasoconstrictor stimuli.…”
mentioning
confidence: 99%